Development of an upscalable HM model for representing advective gas migration through saturated bentonite. (September 2020) - Chittenden, Neil; Benbow, Steven; Bond, Alex; Norris, Simon
Abstract: Understanding gas transport through engineered and natural clays is important for their use in buffers and seals in a range of Geological Disposal Facility (GDF) concepts. Gas migration via processes of multi-phase flow of water and bulk gas, and transport of dissolved gases, have been widely studied and are well understood for traditional porous media. However, models using only these processes are unable to represent the complex behaviour of gas flow in water-saturated clays, where gas migrates through the creation of additional flow paths (via dilatant pathways/tensile fractures). A bespoke fully-coupled hydro-mechanical model representing gas flow through dilating capillaries is presented, where gas in the model is considered to have a separate permeability to water within the saturated bentonite, dependent on the in situ stress conditions. The model permits a coarse spatial discretisation, compared to standard multiphase flow approaches, while still providing a good match to experimental datasets. This should allow for future upscaling (in space and/or time), which may be required if such modelling is necessary in a performance assessment (PA) or GDF safety case context. The model has been tested against small-scale laboratory experiments investigating gas flow through saturated MX-80 bentonite samples as part of participation in Task A of the DECOVALEX-2019 project, and has provided useful experience in the interpretation of the experimental configuration and its representation in models. Good agreement of the model results to the experimental data can be obtained after calibration of a few key parameters, which also provide a good match to an additional historical dataset. The significance of these gas flows is considered in a PA context and potential future improvements are discussed. Highlights: Gas transport in water-saturated bentonite/clays. Novel upscaled model developed for Task A of the DECOVALEX-2019 project. Upscaled hydro-mechanical model representing gas flow through dilating capillaries.